Online and Distance Learning Research in The Last 30 Years: Real Contribution in Physics Learning (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2022)
Learning systems in emergencies, can be implemented by making online-based learning or distance learning. This study compares the top 100 citations of online learning and distance learning publications and analyzes their real contribution in physics learning from 1992 to 2021. This study uses bibliometric analysis and literature review. The findings of this study include: 1) The trend of online learning topics is more consistently rising and has a higher value than distance learning every year, 2) The most frequently used keywords are online learning, and distance metrics learning, the United States has the highest contribution over the last thirty years, 3) The type of document that is often used is articles, 4) The highest average citation per paper per year is in 2020, 5) Both topics demonstrate the superiority of contributions to studying physics. The real contributions in physics are to make learning more flexible, train students' independence, train technology, deepen understanding of concepts and make learning more efficient. More intensively, further research can be done by comparing other learning systems applied in physics learning.